A invisibilidade da diferença surda em pessoas estigmatizadas: um estudo de caso no município de Araguaína – TO - Rodrigues, Judite Fernandes Nunes (Universidade Federal do Tocantins, 2023)
This study aimed to present obstacles observed in the life of a deaf student, stigmatized by a diagnosis of multiple disabilities, within the inclusive school environment. Some procedures for achieving the goal were; conceptualize deaf difference, discuss possible stigmas in the form of multiple disability diagnosis and present some narratives of occurrences in the life of the deaf student, the focus of the study. For this purpose, exploratory research used as a method for data collection, using tools such as access to documents that inform the student's profile, interviews, questionnaires and observations in different school environments in their daily lives. The student's interaction in the school routine happens from a body reading, the use of some conventional signs and a body mimesis with those involved. Despite this, there is resistance from the school and the family to admit the student's deafness, which has this difference canceled out when it comes to the implementation of an education based on sign language. Overlaid on the student on a children's school activity, probably due to the marks it carries on the body by imposition and normalization. From the data analysis, it was possible to realize the importance of fighting for the implementation of an educational pedagogy based on the socio-linguistic-cultural specificity of the deaf, which contemplates their presence in its structural elaboration. Finally, through the whole study, it was possible to confirm that it is important that practices that promote invisibility, stigma and exclusion to eliminate from the school space. May the deaf be references among themselves, through the presence of deaf managers and teachers in the school. Let the educational process of the deaf start from the perspective of the deaf themselves.